Active protection of fiber-reinforced polymer-wrapped reinforced concrete structures against corrosion - Gadve, S.; Mukherjee, Abhijit; Malhotra, S. (NACE International, 2011)
Large numbers of reinforced concrete (RC) structures that have been damaged from corrosion of steel reinforcements are rehabilitated with fiber-reinforced polymer (FRP) composites. This paper investigates active protection of the steel embedded in concrete that is treated with surface-bonded carbon FRP. The electrically conductive carbon fiber is used as an anode while the reinforcing bar is used as a cathode. Concrete cylinder specimens with embedded steel bars are immersed in salt water, and anodic current is passed through the reinforcement to initiate cracking in concrete as a result of accelerated corrosion of steel. Carbon FRP sheets have been bonded adhesively to the cylinders. The adhesive has been modified to impart electrical conductivity. Specimens were exposed to a highly corrosive environment for a specified time. Pullout strength, mass loss, potentiodynamic scans, and the half-cell potential of steel are reported as metrics of performance of the samples. The proposed technique has been very effective in retarding the corrosion of steel.